High performance liquid chromatography as a prospective method for determining chlorambene - Maga, I.M. (Problems of Environmental Biotechnology, 2021)
Chloraben derivatization with 4-nitrophenyldiazonium was performed. The extraction of azoderivative by various extractants has been studied. The chromatography conditions were studied: the composition of the mobile phase, the ratio of components, the feed rate of the eluent, chromatographic parameters. A method for the determination of chloramben by the method of HPLC, has been developed, and the limits of the linear dependence of of the chromatographic peak on the concentration of chloramben. The technique is tested on model solutions.